Facile synthesis of a novel genetically encodable fluorescent α-amino acid emitting greenish blue light. Issue 83 (18th September 2020) - Gupta, Aakash; Garreffi, Brian P.; Guo, Maolin
Abstract : A novel genetically encodable fluorescent l -α-amino acid 4-phenanthracen-9-yl-l -phenylalanine (Phen-AA) that emits greenish blue light and can be imaged in live cells has been synthesized under mild conditions in 3 steps with reasonably good yield. Abstract : We report the facile synthesis and characterization of a novel fluorescent α-amino acid 4-phenanthracen-9-yl-l -phenylalanine (Phen-AA) (5 ) that emits greenish blue light in the visible region. This genetically encodable l -α-amino acid has excellent photostability with a 75% quantum yield. It readily gets into human cells, being clearly imaged upon 405 nm laser excitation. The synthetic procedure is resistant to racemization and only involves three simple steps which use mild conditions and generate the Phen-AA in reasonably good yield. It may find broad applications in research, biotechnology, and the pharmaceutical industry.